KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU SEKOLAH DASAR YANG TERSERTIFIKASI PADA PEMBELAJARAN SAINS - Kalu, Muhammad Ridwan (JSTT, 2016)
The objektive of the research was to analyze pedagogical and profesional competence of certified elementary school teachers on science learning. The research subjecs were 16 teachers. The research method employed was qualitive descriptive by using survey data collected by questionnare, observation and interview. The research result showed hat the pedagogical competence of certified elementary school teachers in science learning in regional I and regional II Tanantovea sub district with observation result reached 48% and questionnare was 76,12%. The competence of the professional had haved on observation 45,97% and questionnare was 66,02%. The pedagogical competence of certified elementary school teacher on science learning in regional I and regional II Tanantovea sub district was good enough category. The professional competence of certified elementary school teachers on science learning was in good enough category. Â Â